Urgensi Pendidikan Agama Hindu Dalam Membentuk Karakter Religius Pada Anak Di Abad 21 - Ketut Agus Nova (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
21st Century Learning with the presence of various technologies in the world of education, requires students to be creative, innovative, think critically and metacognitive and so that students have the ability to communicate and work collaboratively, with the hope that the knowledge and skills acquired can be used as provisions for living in a society that has character both locally and globally and can be personally and socially responsible. Religious character development can be done through Hindu religious education. Hindu religious education is a way of life that contains a number of ideas, values and norms that should be a guide in thinking, speaking and behaving, in order to realize the harmony of its people in all dimensions.